Safer Conception Needs for HIV Prevention among Female Sex Workers in Burkina Faso and Togo. (22nd October 2014) - Schwartz, Sheree R.; Papworth, Erin; Ky-Zerbo, Odette; Anato, Simplice; Grosso, Ashley; Ouedraogo, Henri Gautier; Ketende, Sosthenes; Pitche, Vincent Palokinam; Baral, Stefan
Abstract : Background . Reproductive health programming for female sex workers (FSW) may include contraceptive services but rarely addresses safer pregnancy planning. Methods . Adult FSW were enrolled into a cross-sectional study across four sites in Burkina Faso and Togo using respondent-driven sampling. Sociobehavioral questionnaires and HIV counseling and testing were administered. Sample statistics and engagement in HIV treatment were described and compared using Chi-squared statistics. Results . 1, 349 reproductive-aged FSW were enrolled from January to July 2013. Overall, 267 FSW (19.8%) were currently trying to conceive. FSW trying to conceive were more likely to test positive for HIV at enrollment as compared to women not trying to become pregnant (24.5% versus 17.7%, P < 0.01 ); however awareness of HIV status was similar across groups. Among FSW trying to conceive, 79.0% (211/267) had previously received HIV testing, yet only 33.8% (23/68) of HIV-infected FSW reported a previous HIV diagnosis. Overall 25.0% (17/68) of HIV-infected FSW trying to conceive were on antiretroviral therapy. Conclusion . FSW frequently desire children. However engagement in the HIV prevention and treatment cascade among FSW trying to conceive is poor potentiating periconception transmission risks to partners and infants. Programs to facilitate earlier HIV diagnosis for FSW and safer conception counseling are needed as components of effective combination HIV prevention services.